PENDIDIKAN AGAMA DALAM KULTUR SEKOLAH DEMOKRATIS: Potensi Membumikan Deradikalisasi Agama di Sekolah - Jannet, Herly Jannet (WALISONGO, 2015)
This study aimed in general to determine and describe the religious education in ademocratic school culture is one of potential strategies in disseminating religious deradicalizationin schools. Applying qualitative naturalistic approach with case study,this study focused the location in Christian High School Urimessing Ambon. Theobject of this research was the all democratic phenomena found in the process ofteaching and learning of Christian education. The results of this study can bedescribed as follows: religious education in a democratic school culture has thepotential to disseminate de-radicalization because the learning process optimizedthe attitude of critical thinking on freedom, independence, and accountability thatwere assumed to build the belief, attitude and norm of student to: (1) deepen andbelieve their own religious teachings; (2) commit to transform their religiousteacgings in their daily life, both individually and socially; and (3) become the realwho got off from violence and anarchy in realizing their objectives.***Penelitian ini bertujuan untuk menemukan dan mendeskripsikan PendidikanAgama dalam kultur sekolah demokratis sebagai salah satu strategi membumikanderadikalisasi agama di sekolah. Metode penelitian yang digunakan adalah kualitatifnaturalistik dengan strategi studi kasus dan mengambil tempat penelitian diSMA Kristen Urimessing Ambon. Objek penelitian ini adalah keseluruhan gejalademokratis dalam proses belajar mengajar Pendidikan Agama Kristen. Hasil penelitiandapat dideskripsikan sebagai berikut, Pendidikan Agama dalam kultursekolah demokratis berpotensi membumikan deradikalisasi, karena dalam prosesbelajar mengajar mengoptimalkan sikap kebebasan berpikir kritis, kemandirian,dan akuntabilitas sehingga dapat membentuk keyakinan, sikap dan norma pesertadidik untuk: (1) mendalami dan meyakini ajaran agamanya sendiri; (2) berkomitmenmentransformasikan ajaran agamanya secara baik dalam kehidupanpribadi maupun sosial bermasyarakat; dan (3) memberi teladan secara konkrettidak terjebak menggunakan kekerasan dan anarkisme dalam mewujudkankeinginan.